KONTRIBUSI INDONESIA DALAM PENGIRIMAN PASUKAN PERDAMAIAN PADA MISI MARITIME TASK FORCE (MTF) UNITED NATIONS INTERIM FORCE IN LEBANON (UNIFIL) - Salsa Desliana Alya Putri; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The conflict that occurred in Lebanon in 2006 caused civilian and military casualties as well as the destruction of civilian infrastructure and massive displacement due to Israeli attacks on countries in the Middle East. The United Nations formed a peacekeeping operation, namely the United Nations Interim Force In Lebanon (UNIFIL) with the aim of maintaining peace in Lebanon. This study uses qualitative methods with data collection methods in the form of documentary studies. Documentary studies are conducted by collecting and analyzing written documents or pictures from interviews. This study uses the Neorealist Perspective and the theory of Naval Diplomacy. This theory explains naval diplomacy in Maritime Task Force missions.. Indonesia has a global vision as stated in the fourth paragraph of the Preamble to the 1945 Constitution, namely "to participate in carrying out world order based on freedom, eternal peace and social justice". This made Indonesia's initiative to send peacekeeping troops to Lebanon in the current situation. Indonesia's contribution in sending peacekeepers to Lebanon since 2006 and began sending the Navy on Maritime Task Force (MTF) missions in 2009. This mission aims to support the Lebanese Navy in monitoring Lebanese territorial waters, illegal activities such as weapons smuggling and trade in goods Prohibited goods pass through the Lebanese sea. There are 5 countries that have contributed to the MTF mission, namely Indonesia, Germany, Turkey, Greece and Bangladesh. This mission also carried out joint exercises between the Lebanese Navy so that the Lebanese army could defend its country's territory independently. Keywords: Peacekeepers, Naval Diplomacy, Maritime Task Force, United Nations Interim Force In Lebanon.